Circadian regulation of the transcriptome in a complex polyploid crop. - Hannah Rees; Rachel Rusholme-Pilcher; Paul Bailey; Joshua Colmer; Benjamen White; Connor Reynolds; Sabrina Jaye Ward; Benedict Coombes; Calum A Graham; Luíza Lane de Barros Dantas; Antony N Dodd; Anthony Hall (PLoS Biology)
The circadian clock is a finely balanced timekeeping mechanism that coordinates programmes of gene expression. It is currently unknown how the clock regulates expression of homoeologous genes in polyploids. Here, we generate a high-resolution time-course dataset to investigate the circadian balance between sets of 3 homoeologous genes (triads) from hexaploid bread wheat. We find a large proportion of circadian triads exhibit imbalanced rhythmic expression patterns, with no specific subgenome favoured. In wheat, period lengths of rhythmic transcripts are found to be longer and have a higher level of variance than in other plant species. Expression of transcripts associated with circadian controlled biological processes is largely conserved between wheat and Arabidopsis; however, striking differences are seen in agriculturally critical processes such as starch metabolism. Together, this work highlights the ongoing selection for balance versus diversification in circadian homoeologs and identifies clock-controlled pathways that might provide important targets for future wheat breeding.